(untitled) (Research, Society and Development, 2023)
Throughout history, the use of electricity has become increasingly present and essential for society, playing a key role in meeting the needs of lighting, heating, transport, production and distribution of various industrial materials. In this work, a descriptive and exploratory literature review was carried out addressing the topic of renewable electricity in the state of Maranhão. Articles, abstracts and dissertations available online were used as research sources. The objective was to carry out an in-depth analysis of the potential in the territory of Maranhão in relation to renewable energy sources for electricity generation. The region has a favorable topography, hydrography and climate, which makes it suitable for the exploration of a variety of renewable energy sources. In 2013, the total electricity generation capacity installed in the state was 2,309 MW, from hydroelectric, tidal, wind and solar sources. These numbers show the relevant energy potential of Maranhão for the generation of renewable electricity.